Effects of flipped learning on the students’ interest and learning experiences in physics - Raheem-Folayinka, Ganiyat Pelumi; Babajide, Veronica Folasade T.; Raheem, Isiaka Ayobi (Journal of Education For Sustainable Innovation, 2024)
The study examined the effect of flipped learning on the student’s interest in Physics and learning experiences between a flipped classroom and a conventional classroom. A quasi-experimental pre-test/post-test control group design was adopted for this study. An intact class sample of 45 students as the experimental group and 50 control group of SS 2 students that offered Physics were used for this study from two senior secondary schools in Lagos State. The Questionnaire with a reliability coefficient (r) of 0.84 was instrumentally used for data collection for this study. the study’s data were analyzed to get frequency counts, mean, and standard deviation and interpreted at p < 0.05 level of significance. This study’s results revealed that the flipped learning method significantly affected students' interest in Physics, and students acquired more excellent learning experiences whenever they were exposed to a flipped classroom than a conventional classroom. Concerning the findings of this study, it is highly recommended that secondary school teachers should always be ready to utilise innovative teaching techniques that will boost students’ interest in learning Physics and other subjects exceptionally, and creatively stimulate students’ learning experiences in all ramifications among others.